Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.
DOI: 10.1109/apec.2005.1452904
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase cooling method using R134a refrigerant to cool power electronic devices

Abstract:  This paper presents a two-phase cooling method using R134a refrigerant to dissipate the heat energy (loss) generated by power electronics (PE) such as those associated with rectifiers, converters, and inverters for a specific application in hybrid-electric vehicles (HEVs). The cooling method involves submerging PE devices in an R134a bath, which limits the junction temperature of PE devices while conserving weight and volume of the heat sink without sacrificing equipment reliability.First, experimental tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…During microcooler testing at the Division of Applied Mechanics and Energy Conversion of the KU Leuven this flow regime was confirmed using R134a, a common refrigerant. Since the di↵erence in permittivity between liquid and gaseous R134a is only 0.5 [20], as well as for safety reasons, water and air were preferred for the testing (and simulating) of the sensors. Testing of the sensors is further discussed in section 4.…”
Section: Modelling and Simulationmentioning
confidence: 99%
“…During microcooler testing at the Division of Applied Mechanics and Energy Conversion of the KU Leuven this flow regime was confirmed using R134a, a common refrigerant. Since the di↵erence in permittivity between liquid and gaseous R134a is only 0.5 [20], as well as for safety reasons, water and air were preferred for the testing (and simulating) of the sensors. Testing of the sensors is further discussed in section 4.…”
Section: Modelling and Simulationmentioning
confidence: 99%
“…Another study by Campbell et al [32] and Ayers et al [33] showed that thermal management of power electronics is vital to the operation of hybrid electronic vehicles. They also suggested that R134a has no damaging effect on the normal operation of the submerged IGBT.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%
“…Life tests with capacitors, an insulated gate bipolar transistor (IGBT), and a gate-driver printed circuit board showed no adverse affects when in direct contact with the refrigerant. The life tests have been conducted over a period of 15 months with periodic functional tests of the circuitry and visual inspections of the components and wiring occurring almost monthly [4].…”
Section: Introductionmentioning
confidence: 99%